2015
DOI: 10.1088/1674-1056/24/7/076802
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption behavior of Fe atoms on a naphthalocyanine monolayer on Ag(111) surface

Abstract: (闫凌昊) a) , Wu Rong-Ting(武荣庭) a) , Bao De-Liang(包德亮) b) , Ren Jun-Hai(任俊海) a) , Zhang Yan-Fang(张艳芳) a) , Zhang Hai-Gang(张海刚) c) , Huang Li(黄 立) a) , Wang Ye-Liang(王业亮) a)b) , Du Shi-Xuan(杜世萱) a)b) † , Huan Qing(郇 庆) a)b) ‡ , and Gao Hong-Jun(高鸿钧) a)b) a)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Metal phthalocyanine (MPc) and metal porphyrin (MP) have been synthesized and used as building blocks and functional units for various nanoscale applications, such as chemosensors, active nanocatalysts, organic light-emitting diodes, organic solar cells, and biomedical applications. , Metalation of phthalocyanine (H 2 Pc) or porphyrin (H 2 P), namely, the incorporation of a metal atom at the center of the H 2 Pc or H 2 P molecule, is one way to produce MPcs or MPs with novel physical and chemical properties. Compared to the conventional synthesis methods that combine certain precursors under specific conditions, the in situ on-surface metalation has advantages such as mild conditions , and high yield . Moreover, in situ on-surface metalation of H 2 Pc, H 2 P, and their derivatives is a superior technique toward the realization of low-dimensional functionalized materials of organometallic compounds. …”
Section: Introductionmentioning
confidence: 99%
“…Metal phthalocyanine (MPc) and metal porphyrin (MP) have been synthesized and used as building blocks and functional units for various nanoscale applications, such as chemosensors, active nanocatalysts, organic light-emitting diodes, organic solar cells, and biomedical applications. , Metalation of phthalocyanine (H 2 Pc) or porphyrin (H 2 P), namely, the incorporation of a metal atom at the center of the H 2 Pc or H 2 P molecule, is one way to produce MPcs or MPs with novel physical and chemical properties. Compared to the conventional synthesis methods that combine certain precursors under specific conditions, the in situ on-surface metalation has advantages such as mild conditions , and high yield . Moreover, in situ on-surface metalation of H 2 Pc, H 2 P, and their derivatives is a superior technique toward the realization of low-dimensional functionalized materials of organometallic compounds. …”
Section: Introductionmentioning
confidence: 99%
“…Naphthalocyanine (H 2 Nc), an important class of Pc derivatives with extended π-electronic system, reveals superior optical and electronic properties. ,, Initial investigations about the H 2 Nc molecules on surfaces are mainly focused on graphite , and insulators. , Recently, H 2 Ncs on metallic substrates such as Au(100), Au(111), , and Ag(111) , have been investigated. Among these studies, the self-assembled structures of densely packed phases such as domain orientations , and underlying mechanical strains have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…10,11,17−22 Initial investigations about the H 2 Nc molecules on surfaces are mainly focused on graphite 23,24 and insulators. 25,26 Recently, H 2 Ncs on metallic substrates such as Au(100), 27 Au(111), 28,29 and Ag(111) 30,31 have been investigated. Among these studies, the selfassembled structures of densely packed phases such as domain orientations 27,28 and underlying mechanical strains 30 have been studied.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, there have so far been very few studies of the properties of sublimed Nc thin films 11,14,15 ; in fact it has been suggested that Nc cannot be sublimed 13 , although the deposition of monolayer coverages have been reported by a number of groups [16][17][18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…Both molecules strongly adsorb light and the larger molecule, Nc, has a more extended π-conjugation system, resulting in an absorption edge at longer wavelength, in the infrared. Both molecules are highly insoluble, and there have been many studies of derivatives which have additional groups which can promote solubility. , Pc can be sublimed readily, and the resulting thin films have been incorporated into a wide range of organic devices. , However, there have so far been very few studies of the properties of sublimed Nc thin films; ,, in fact it has been suggested that Nc cannot be sublimed, although the deposition of monolayer coverages has been reported by a number of groups. Consequently it has not been possible to characterize systematically the properties of sublimed Nc thin films.…”
Section: Introductionmentioning
confidence: 99%